2015
DOI: 10.1002/ccd.26121
|View full text |Cite
|
Sign up to set email alerts
|

Learning curves for transfemoral transcatheter aortic valve replacement in the PARTNER‐I trial: Success and safety

Abstract: By end of trial, a consistent low risk of adverse events was achieved after ∼26 cases. However, these improved results were due to change in patient risk profile; outcomes were not linked to the technical performance learning curve. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 16 publications
4
48
1
Order By: Relevance
“…They concluded that TF-TAVR is preferred for inoperable patients at high risk of noncardiovascular mortality. Unlike TF-TAVR, however, 15,16 we found little evidence of a technical performance learning curve, and no suggestion that a technical learning curve is associated with adverse outcomes or prolonged postprocedure hospitalization after adjusting for patient factors.…”
Section: Discussioncontrasting
confidence: 60%
“…They concluded that TF-TAVR is preferred for inoperable patients at high risk of noncardiovascular mortality. Unlike TF-TAVR, however, 15,16 we found little evidence of a technical performance learning curve, and no suggestion that a technical learning curve is associated with adverse outcomes or prolonged postprocedure hospitalization after adjusting for patient factors.…”
Section: Discussioncontrasting
confidence: 60%
“…There are learning curves associated with TAVR . For instance, nonfemoral TAVR involves an important learning process, with 30–45 cases needed to reach a plateau for procedure time and device success .…”
Section: Structural Program Requirementsmentioning
confidence: 99%
“…Prior to expanding into alternative access, a new TAVR program should first complete at least 80 TAVRs using transfemoral access with an STS/ACC TVT Registry 30‐day all‐cause mortality above the bottom 25% of all TAVR programs for two consecutive quarters/year. The writing committee's consensus regarding the required 80 TAVR procedures was based on information from referenced articles and expert opinion . Alliances should be established between low‐volume, high‐quality programs serving geographic isolated areas, or programs caring for underserved populations and high‐volume, high‐quality programs to care for patients needing alternative access and the higher‐risk complex patient population needing TAVR.…”
Section: Criteria For Establishing a Tavr Program And Maintenance Of mentioning
confidence: 99%
“…On one hand, there is a substantial increase in experience with TAVI that in turn has improved outcome [19, 20]. On the other, the number of different types and sizes of valve technologies increase as well [21].…”
Section: Introductionmentioning
confidence: 99%